Ciudadanía cultural y migración desde la perspectiva de género (Contextos: Estudios de Humanidades y Ciencias Sociales, 2017)
This article relates communities and transnational spaces in contemporary migration theory. Migration studies have moved from a classic vision marked by the absence of women as migrant subject into another view where the peculiarities of female migration are recognized. The case of Peruvian women in Chile is exemplified, such as matemity at a distance, to the actual practice in a transnational space. Issues of the fundamental rights of immigrants and political rights of citizens are analyzed. Finally, we reflect on the concept of cultural citizenship or political membership in immigration movements.